2013
DOI: 10.3844/ajassp.2013.172.178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Food Color Consumption and Determining Color Type by Thin Layer Chromatography

Abstract: The aim of this research was to investigate the role of the social demographic parameters of the people in charge of the facilities producing pastry, poolak (a type of coin-shaped candy) and rock candy in the consumption of food colors and to determine color type by thin layer chromatography in Shahr-e-kord city in 2011. This research was an interventional-analytical study and its target population is the people in charge of the facilities producing pastry, poolak and rock candy in Shahr-e-kord city. Social de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 14 publications
(17 reference statements)
0
16
0
Order By: Relevance
“…Fruit juice sample was centrifuged at 2500 rpm for 15 minutes. en 5 mL from upper layer was acidified using 10 mL of 2 M glacial acetic acid [15]. en the sheep-wool was put into the conical flask and placed in water bath at 100°C for 1 hr and 30 minutes.…”
Section: Sample Preparation and Colorant Extraction From Fruitmentioning
confidence: 99%
“…Fruit juice sample was centrifuged at 2500 rpm for 15 minutes. en 5 mL from upper layer was acidified using 10 mL of 2 M glacial acetic acid [15]. en the sheep-wool was put into the conical flask and placed in water bath at 100°C for 1 hr and 30 minutes.…”
Section: Sample Preparation and Colorant Extraction From Fruitmentioning
confidence: 99%
“…Similarly, among 70 food items in Arak, Iran, 80% of the samples contained artificial colour additives that are banned as per by the National Iranian Standards [10]. Another study conducted by Farzianpour et al showed that 6.52% of the pastry, poolak, and rock candy samples at Shahr-e-kord City, Iran, contained forbidden artificial food colours [11]. In a study conducted at Rawalpindi Cantt it was found that among 73 samples of sweetmeats and confectioneries, 46.57% contained nonpermitted colours [6].…”
Section: Spectroscopic Analysismentioning
confidence: 99%
“…These colours can also be categorized as permitted and nonpermitted food colours [9]. In recent years many synthetic dyes have been increasingly used to substitute natural colours or to achieve certain desirable qualities such as improved appearance, high colour intensity, colour stability and uniformity [10][11][12][13][14]. Compared to natural colours, these synthetic dyes are low in cost, resistant to light, temperature, oxygen, pH changes, and can be used without further processing [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, environmental activities play a strategic role in product design planning and working process, senior managers' support for the organization and manufacturing activities and also, influence the organization's manufacturing performance (Tseng, 2011a;2011b;Tzeng and Opricoric, 2003;Farzianpour et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%